Synthesis and anti-melanoma effect of 3-O-prenyl glycyrrhetinic acid against B16F10 cells via induction of endoplasmic reticulum stress-mediated autophagy through ERK/AKT signaling pathway - Nazir, Lone A.; Shahid, Naikoo H.; Amit, Kumar; Umar, Sheikh A.; Rajni, Sharma; Bharate, Sandip; Sangwan, Pyare L.; Tasduq, Sheikh Abdullah (Frontiers in Oncology, 2022)
Melanoma is an aggressive form of cancer with poor prognosis, survival rates and limited therapeutic options. Here we reported the anti-melanoma effect of 3-O-prenyl glycyrrhetinic acid (NPC-402) a derivative of Glycyrrhetinic acid, from a reputed medicinal plant Glycyrrhiza glabra against B16F10 cells. We studied the cytotoxic effect of NPC-402 on melanoma cells and investigated the role of MAP kinase, AKT axis, ER–stress/UPR mediated autophagy as involved signalling cascade by studying specific marker proteins. 4 Phenyl Butyric Acid (4PBA, a chemical chaperon) and siRNA knockdown of CHOP/GAD153 blocked NPC-402 mediated autophagy induction, thus confirmed the role of ER stress and autophagy in melanoma cell death. NPC-402 -induced oxidative stress and apoptosis in melanoma cells, which was effectively mitigated by treatment with N-acetyl cysteine (NAC). In- vivo studies showed that intraperitoneal (IP) injection of NPC-402 @ 10mg/kg (5 days in one week), significantly retarded angiogenesis in matrigel plug assay and reduced the tumor size and tumor weight without causing any significant toxic manifestation in C57BL/6J mice. We conclude that NPC-402 has a high potential to be developed as a chemo-therapeutic drug against melanoma.